2006
DOI: 10.1002/chem.200600530
|View full text |Cite
|
Sign up to set email alerts
|

Coupling–Isomerization Synthesis of Chalcones

Abstract: The Sonogashira coupling of electron-deficient (hetero)aryl halides 1 and (hetero)aryl or alkenyl 1-propargyl alcohols 2 does not terminate at the stage of the expected internal propargyl alcohols, but rather gives rise to the formation of alpha,beta-unsaturated ketones 3 with a variety of acceptor substituents. This new domino reaction, a coupling-isomerization reaction (CIR), can be rationalized as a sequence of rapid Pd/Cu-catalyzed alkynylation followed by a slow amine-base-catalyzed propargyl alcohol-enon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(35 citation statements)
references
References 67 publications
0
35
0
Order By: Relevance
“…Domino synthesis of spirobenzofuranones and spirodihydroindolones: In recent years we have developed consecutive multicomponent syntheses of pharmaceutically relevant heterocycles [10,11] initiated by a coupling-isomerization reaction [10,12] (CIR) (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Domino synthesis of spirobenzofuranones and spirodihydroindolones: In recent years we have developed consecutive multicomponent syntheses of pharmaceutically relevant heterocycles [10,11] initiated by a coupling-isomerization reaction [10,12] (CIR) (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Kinetics of the model reaction under conventional heating revealed that, for the rate-limiting isomerization step, dipolar aprotic solvents such as acetonitrile and DMF give rise to fastest conversions and almost quantitative yields. [5] However, under dielectric heat-ing the yields in acetonitrile never exceeded 67 % (entries 1-8). Increasing the effective temperature inside the reaction vessel from 120 to 150 8C led to decreased yields of 4a (entries 3 and 4), whereas, a shorter reaction time at higher temperature gave comparable yields (entry 5).…”
mentioning
confidence: 98%
“…Kinetic studies of the isomerization step show that the reaction proceeds fastest at a more than five-fold excess of amine base and in a dipolar aprotic medium. [5] Although the CIR is a mild and versatile synthesis of chalcones it has some inherent scope limitations and shortcomings under the conditions of conductive heating. Besides a limited choice of the reaction media, a relatively large excess of base, and long reaction times (16-24 h), most strikingly, the demand for an activating electron-deficient (hetero)aryl halide as a coupling partner is less advantageous.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7,8] Indeed, compared with the traditional intramolecular Diels-Alder reaction, the presence of an allene motif enhances the diversity of reaction possibilities, thus serving as a potentially diversifiable approach to fused rings systems [Eqs. (1) to (4), Figure 1].…”
mentioning
confidence: 99%